Increased Activity Of Mature Osteoblast from Rat Bone Marrow-Mesenchymal Stem Cells tn Osteogenic Medium Exposed to Melatonin - Purnama, Yugi Hari Chandra; Mastutik, Gondo; Putra, Suhartono Taat (Folia Medica Indonesiana, 2018)
Exposure to melatonin in the cultures of Bone Marrow Mesenchymal Stem Cells (BM-MSCs) in osteogenic medium is able to induce mesenchymal stem cells and preosteoblasts into active osteoblasts via several transduction signals such as ERK 1/2. Previous studies used a single dose of 50 nM and a physiological dose of 20-200 pg/ml. The objective of the study was to obtain an optimal dose of melatonin that enhances osteoblast activity by increasing the expression of ERK1/2 and ALP levels in the culture of Rat Bone Marrow Mesenchymal Stem Cells (BM-MSCs) in osteogenic medium. This study was an in vitro experimental laboratory study using BM-MSCs from rat femoral bone grown on osteogenic medium without or with exposure to melatonin in doses of 0, 50, 100, 150 nM for 21 days. BM-MSCs were characterized by immunocytochemical techniques (CD45- and CD 105+) and ERK 1/2 expression was checked 24 hours after exposure to melatonin, while ALP levels were examined on day 21 using ELISA technique. ERK 1/2 expression on BM-MScs exposed to melatonin in doses 0, 50, 100, and 150 nM were respectively 0.087, 0.095, 0.081, and 0.079. Mean ERK 1/2 expression in various groups showed a decrease along with increasing doses of melatonin. Among the four treatment groups, the administration of melatonin in a dose of 50 nM resulted in highest mean ERK 1/2 expression. ALP levels in BM-MSCs exposed to melatonin doses of 0, 50, 100, and 150 nM were 0.128; 0.130; 0.117, and 0.111 ng/ml respectively. Data showed that decreasing mean ALP levels occurred along with the addition of melatonin dose. In conclusion, the administration of melatonin 50 nM is the optimal dose to increase the differentiation of cultured rat BM-MSCs into active osteoblasts.